دعائم الإدارة المدرسية الفاعلة بالمدارس الأهلية بمنطقة مكة المكرمة من وجهة نظر المديرين - السليمي، خالد بن سعد بن محمد (جامعة المنوفية - كلية التربية, 2016)
يهدف البحث إلى التعرف على درجة توافر دعائم الإدارة المدرسية الفاعلة في المدارس الأهلية بمنطقة مكة المكرمة من وجهة نظر المديرين، واستخدم الباحث المنهج الوصفي التحليلي، تم اختيار عينة البحث بالطريقة العشوائية من مديري المدارس الأهلية والبالغ عددهم (333) مديرا، مقسمة إلى (35) مديرا كعينة استطلاعية من خارج عينة البحث الأساسية لتكون عينة البحث الأساسية (298)، اعتمد الباحث على استمارة الاستبيان كأداة لجمع البيانات، وقد استخدم الباحث الاستبيان الذي أعده إبراهيم محمد شعيب عام (2008م)، ومن أهم الاستنتاجات التي توصل إليها الباحث تتوافر دعائم الإدارة المدرسية الفاعلة بالمدارس الأهلية بالمملكة العربية السعودية بنسبة مرتفعة بلغت (82,22%)، كما جاء محور التجهيزات المدرسية في مقدمة دعائم الإدارة المدرسية الفاعلة بالمدارس الأهلية، يليه أعضاء الهيئة التدريسية، يلية القيادة التربوية، يليه المناخ المدرسي، يليه الأنشطة التربوية اللاصفية، يليه العلاقة مع المجتمع المحلي، وأخيرا التحصيل الدراسي.
The effective school management pillars of Makka El Mokaramah public schools from the TEMPprincipals respective \\ The research aims to identify the degree of availability of effective school management pillars of Makka El Mokaramah public school from the TEMPprincipals respective, the researcher used analytical descriptive method, the research sample was chosen by random way from public school TEMPprincipals included(333) principal divided as (35) principas as pilot sample outside the basic research sample so that the basic sample (298) the researcher depend on questionnaire form as a tool to collect data, the research used the questionnaire prepared by Ibrahim Mohammed Shoaib (2008), the most important results the availability of effective school management pillars in public school in Kingdoom of Saudi Arabia with high percent of (82.22%), also the aspect of school supplies came in first place of the effective school management pillars of public school ,second came the teaching staff, tan came educational leadership, school environment, tan no class educational activities, relation with local community , and finally school achievement.
Keywords: مكة المكرمة -- المدارس الأهلية -- الإدارة المدرسية